2016
DOI: 10.1016/j.jcmgh.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Arg-Gly-Asp-Binding Integrins Reduce Development of Pancreatic Fibrosis in Mice

Abstract: Background & AimsPancreatic stellate cells (PSCs) regulate the development of chronic pancreatitis (CP) and are activated by the cytokine transforming growth factor β (TGFB). Integrins of the αv family promote TGFB signaling in mice, probably by interacting with the Arg-Gly-Asp (RGD) sequence of the TGFB latency-associated peptide, which frees TGFB to bind its cellular receptors. However, little is known about the role of integrins in the development of CP. We investigated the effects of small-molecule integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
5
23
0
1
Order By: Relevance
“…Because the severity of NASH‐induced liver fibrosis is the main predictor of liver‐related mortality in NASH, it is critically important to identify the mechanisms responsible for fibrosis development in NASH and to develop treatments that are effective in the prevention and reversal of fibrosis. Recently, RGD‐binding integrins were found to play an important role in the development of organ fibrosis, and several studies, including a study from our laboratory, demonstrated the efficacy of a potent small‐molecule synthetic analog of the RGD peptide (CWHM‐12) in mouse‐injury models of liver, lung, muscle, and pancreatic fibrosis . Here, by assessing CWHM‐12 in a mouse model of NASH, we provide evidence supporting the role of RGD‐binding integrins in the pathogenesis of NASH‐induced liver fibrosis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Because the severity of NASH‐induced liver fibrosis is the main predictor of liver‐related mortality in NASH, it is critically important to identify the mechanisms responsible for fibrosis development in NASH and to develop treatments that are effective in the prevention and reversal of fibrosis. Recently, RGD‐binding integrins were found to play an important role in the development of organ fibrosis, and several studies, including a study from our laboratory, demonstrated the efficacy of a potent small‐molecule synthetic analog of the RGD peptide (CWHM‐12) in mouse‐injury models of liver, lung, muscle, and pancreatic fibrosis . Here, by assessing CWHM‐12 in a mouse model of NASH, we provide evidence supporting the role of RGD‐binding integrins in the pathogenesis of NASH‐induced liver fibrosis.…”
Section: Discussionsupporting
confidence: 54%
“…CWHM‐12 was delivered by continuous infusion at 100 mg/kg/day (in 50% dimethyl sulfoxide [DMSO], 50% H 2 O) using Alzet mini‐osmotic pumps (Durect, Cupertino, CA) implanted subcutaneously in mice starting at the end of week 6 for the duration of the final 4 weeks. This dosing regimen has been demonstrated to be efficient in reducing fibrosis in other injury models . Minipumps with vehicle (50% DMSO, 50% H 2 O) were implanted in CDAHFD and chow diet control groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 As the main transmembrane cell adhesion and signaling receptor proteins, about half of integrin heterodimers connect the cytoskeleton with the extracellular matrix (ECM) via binding to Arginine-Glycine-Aspartic Acid (RGD) sequence. 26, 27 Integrins play pivotal roles in cancer progression, such as proliferation, invasion and metastasis, through binding to ECM components. 28 Some integrins, including αvβ3 and αvβ5, are overexpressed in neovasculature and some tumors including ovarian cancer (OvCa).…”
Section: Introductionmentioning
confidence: 99%
“…Treating mice with the αV integrin inhibitor CWHM-12 both prevented pancreatic fibrosis and reversed established pancreatic fibrosis in the repetitive injury model 31 . An inactive stereoisomer had no effect.…”
Section: Pathophysiology Of Chronic Pancreatitismentioning
confidence: 96%